Correction: Hypermethylation of BMPR2 and TGF-β Promoter Regions in Tibetan Patients with High-Altitude Polycythemia at Extreme Altitude - Quzong Zhaxi; Luobu Gesang; Ju Huang; Yangzong Suona; Bai Ci; Zhuoga Danzeng; Rui Zhang; Binyun Liu (Biochemical Genetics, 2025)

Hypermethylation of BMPR2 and TGF-β Promoter Regions in Tibetan Patients with High-Altitude Polycythemia at Extreme Altitude - Quzong Zhaxi; Luobu Gesang; Ju Huang; Yangzong Suona; Bai Ci; Zhuoga Danzeng; Rui Zhang; Binyun Liu (Biochemical Genetics, 2025)

C1q/Tumor Necrosis Factor-Related Protein-9 Enhances Macrophage Cholesterol Efflux and Improves Reverse Cholesterol Transport via AMPK Activation - Xiaosu Song; Gaizhen Liu; Yunfei Bin; Rui Bai; Bin Liang; Huiyu Yang (Biochemical Genetics, 2025)
Cholesterol efflux from foam cells in atherosclerotic plaques is crucial for reverse cholesterol transport (RCT), an important antiatherogenic event. ATP-binding cassette (ABC) transporters, ABCA1 and ABCG1, are key receptors in the cholesterol efflux pathway. C1q/tumor necrosis factor-related protein-9 (CTRP9) is a newly discovered adipokine and exhibits an atheroprotective activity. However, the role of CTRP9 in RCT still remains unknown. In this work, we investigated the effect of subcutaneous administration of CTRP9 protein on RCT and atherosclerotic lesion formation in ApoE −/− mice fed with a high-fat diet. CTRP9-dependent regulation of cholesterol efflux and ABC transporters in RAW 264.7 foam cells was determined. Our results showed that CTRP9 protein decreased atherosclerotic lesions, increased cholesterol efflux, and upregulated liver ABCA1 and ABCG1 expression in ApoE −/− mice. CTRP9 treatment dose-dependently increased mRNA and protein expression of ABCA1, ABCG1, and LXR-α in RAW 264.7 foam cells. Moreover, the expression and phosphorylation of AMPK was potentiated upon CTRP9 treatment. Notably, CTRP9-induced cholesterol efflux and upregulation of ABCA, ABCG1, and LXR-α were impaired when AMPK was knocked down. AMPK depletion restored cholesterol accumulation in CTRP9-treated RAW 264.7 cells. Taken together, subcutaneous injection is an effective novel delivery route for CTRP9 protein, and exogenous CTRP9 can facilitate cholesterol efflux and promote RCT in an animal model of atherosclerosis. The atheroprotective activity of CTRP9 is mediated through the activation of AMPK signaling.

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

LncRNA MIR4697HG Alleviates Endothelial Cell Injury and Atherosclerosis Progression in Mice via the FUS/ANXA5 Axis - Xue Liu; Rui Huang; Jiye Wan; Tiesheng Niu (Biochemical Genetics, 2024)

SLCO1B1 Polymorphisms are Associated with the Susceptibility to Pulmonary Tuberculosis in Chinese Females - Wei Li; Wei Liu; Xiong Wang; Rui Dou; Zunmin Zhu (Biochemical Genetics, 2024)

Circ_HIPK3 Inhibits H2O2-Induced Lens Epithelial Cell Injury in Age-Related Cataract Depending on the Regulation of miR-495-3p/HDAC4 Pathway - Sihui Chen; Minghong Wang; Rui Jian; Hui Li; Guoli Liu; Cuiyun Zhou; Yan Xiong; Wenqian Wang (Biochemical Genetics, 2023)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Leaf Transcriptome and Weight Gene Co-expression Network Analysis Uncovers Genes Associated with Photosynthetic Efficiency in Camellia oleifera - Zhilong He; Caixia Liu; Xiangnan Wang; Rui Wang; Yun Tian; Yongzhong Chen (Biochemical Genetics, 2021)

MELK Accelerates the Progression of Colorectal Cancer via Activating the FAK/Src Pathway - Guangming Liu; Wei Zhan; Wei Guo; Feng Hu; Junjie Qin; Rui Li; Xin Liao (Biochemical Genetics, 2020)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)

Genetic diversity in the Chinese pangolin (Manis pentadactyla) inferred from protein electrophoresis - Bing Su; Rui-Qing Liu; Ying-xiang Wang; Li-ming Shi (Biochemical Genetics, 1994)